Development of AFRO Water Treatment Equipment - Hafni Hafni; Dedi Wardianto; Asmara Yanto (Jurnal Teknik Mesin, 2023)
Water is a source of life, but it is very easily polluted because water is known as a universal solvent and is able to dissolve many substances. Water pollution is the pollution of water bodies (seas, lakes, rivers, groundwater) caused by human activities. To obtain water that meets water quality standards, it must be supported by an appropriate water treatment system, one of which is the water treatment tool in this research, called AFRO. AFRO works with a reverse osmosis filtration aeration process. Previously, AFRO was developed to treat raw water containing dissolved impurities. However, the results are less than satisfactory, so it needs to be developed further to meet the need for clean water that can be utilized by the community. The development of AFRO in this research is based on the House of Quality (HQ) matrix. From this HQ matrix, a presentation of development priorities was obtained from the previous one in the form of design changes of 16.1%, material changes of 9.6%, processing processes of 14% and energy changes of 9.2%. From the tests that have been carried out, this time AFRO can process raw water from dissolved and insoluble impurities. This tool is also equipped with a solar energy utilization system. The AFRO water treatment process developed consists of (1) chemical process, (2) aeration, (3) filtration, (4) reverse osmosis and (5) disinfection using ultra violet (UV) light.